(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The main objective of the study is to show the nature of the relationship between the carbon footprint tax and sustainable performance, as the problem of the study was embodied in presenting an important topic in the management literature, which is one of the global research trends towards achieving sustainability. To achieve the objectives of the study, the researchers distributed a questionnaire to the customers of Al-Mansour Mall, and the researchers obtained 438 The response was analyzed using the advanced statistical package application SmartPLS V.4) The study reached an important set of conclusions, namely that there is a significant relationship between carbon footprint taxes and dynamic sustainability performance, and that carbon taxes can be effective tools in driving sustainability, and that a comprehensive approach that takes into account the economic, social, and environmental aspects is a necessity. Essential for achieving positive, meaningful and lasting results. The study also presented a set of recommendations, the most important of which is that stakeholders can work together to create a more sustainable future, and achieve a balance between economic considerations and environmental responsibility. Collaboration and commitment to continuous improvement are essential to achieve meaningful and lasting results in the fight against climate change